2017
DOI: 10.14405/kjvr.2017.57.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Blood parameter changes in Korean traditional calves and pigs after foot-and-mouth disease vaccination

Abstract: This study investigated changes in certain blood parameters in calves and pigs after foot-and-mouth disease (FMD) vaccination. In this study, five calves and five pigs were selected from groups of 10 calves and pigs, respectively, and were vaccinated with an FMD vaccine. The remaining animals formed two non-treatment control groups. Blood samples were collected from all animals on the 1st, 3rd, 5th, and 7th days post-vaccination. In the FMD-vaccinated calves and pigs on day 7 post-vaccination, white blood cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In another study, cTn-T, cTn-I, LDH levels in healthy calves were reported as 0.344 ng/mL, 0.03 ng/mL, 959.02 U/L, respectively, and increased in premature calves (Aydoğdu et al, 2016). Similarly the cTn-I, LDH, AST and ALT levels of calves with foot and mouth were reported significantly higher (Tunca et al, 2008;Cha et al, 2017;Salim et al, 2019;Aly et al, 2020). In this case report, the cTn-T, cTn-I, CK-MB, LDH, AST and ALT levels of the calf with myocarditis were 1.00 ng/mL, 26.68 ng/mL, 262.0 U/L, 4503 U/L, 56.6 U/L, 55.3 U/L, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…In another study, cTn-T, cTn-I, LDH levels in healthy calves were reported as 0.344 ng/mL, 0.03 ng/mL, 959.02 U/L, respectively, and increased in premature calves (Aydoğdu et al, 2016). Similarly the cTn-I, LDH, AST and ALT levels of calves with foot and mouth were reported significantly higher (Tunca et al, 2008;Cha et al, 2017;Salim et al, 2019;Aly et al, 2020). In this case report, the cTn-T, cTn-I, CK-MB, LDH, AST and ALT levels of the calf with myocarditis were 1.00 ng/mL, 26.68 ng/mL, 262.0 U/L, 4503 U/L, 56.6 U/L, 55.3 U/L, respectively.…”
Section: Discussionmentioning
confidence: 92%